Structural and Electromagnetic Properties of Lithium Ferrite Manufactured by Extrusion Printing - Lysenko E. N. Elena Nikolaevna; Nikolaev E. V. Evgeny Vladimirovich; Vlasov V. A. Vitaliy Anatolievich; Svirkov Aleksandr Sergeevich A. S.; Surzhikov A. P. Anatoly Petrovich; Sheveleva E. A. Elena Aleksandrovna; Plotnikova I. V. Inna Vasilievna; Artishchev S. A. (2024, 2024)
Title screen